Energy management technology of new microgrid with hybrid virtual energy storage - FU Yuan; WEI Jiahui; ZHANG Xiangyu; LIU Zhuolin; LI Shanxi (Diance yu yibiao)
Simplification of the parameters for flexibility resource utilization is the key for the new microgrid to complete the source-load-storage cooperative optimization. The equivalent models of power-density virtual capacitor and energy-density virtual battery are established for wind power, controllable load, electric vehicle and hydrogen energy storage in the new microgrid. Virtual capacitance, current and state-of-charge are introduced to establish an economic calculation model for a new type of microgrid with multiple types of flexibility resources considering wind and solar uncertainties and hybrid virtual energy storage, which takes into account water purification from seawater desalination loads in microgrids, electricity sales from electric vehicles and hydrogen production revenues as well as the comprehensive operation and maintenance costs. On this basis, the energy management strategy of the new microgrid with hybrid virtual energy storage is proposed, and the virtual capacitance and virtual current are used to call multiple types of flexibility resources, update the virtual charging state of the equipment, and improve the level of cooperative operation of the system. A new microgrid test system is constructed to verify that the proposed control method can significantly improve the cooperative operation of multiple flexibility resources.